Using Multimedia Resources as A Means To Enhance The Creative Potential Of Primary School Students - Vasilevna, Yugay Ekaterina (Indonesian Journal Publisher, 2024)
Modernization of education is aimed not only at changing the content of the subjects studied, but also at changing approaches to teaching methods, expanding the arsenal of teaching methods, activating students' activities during classes and finding ways to solve some problems in the educational process.